An Analysis of Third Year Students of English Department Faculty Languages and Arts UNP Ability in Pronouncing Diphthong of English Words - Mella Fauzia; Zul Amri; Ratmanida Ratmanida (Journal of English Language Teaching, 2020)
The purposes of this study are to know how is the pronunciation of the third year students of English department Universitas Negeri Padang in pronouncing diphthong of English words and what diphthong that mostly mispronounced by the students. This research is quantitative research method. The research population is the third year students; the class of 2015. There were 33 students taken as the research sample which selected through cluster sampling technique. The data were collected through pronunciation test. The students were asked to pronounce the list of diphthong of English words. The pronunciation was recorded through tape recorder. Moreover, there were 48 words in the test. The words represented eight types of diphthong. The pronunciations were analyzed by using Cambridge Advanced Learner Dictionary and also help by two raters. The pronunciations were transcribed in order to answer the research problems. The results of the study show that students’ ability in pronouncing diphthong of English words is sufficient. In addition, the highest percentage of diphthong error is diphthong aʊ (24,81 %). The less percentage error is diphthong ɔɪ (2,90 %).